A Narrative Review of Key Risk Factors for Severe Illness Following SARS-CoV-2, Influenza Virus, and Respiratory Syncytial Virus Infection - Angela Branche; Mayur Ramesh; Beverly Francis (Infectious Diseases and Therapy)
Abstract Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza, and respiratory syncytial virus (RSV) are highly infectious respiratory viruses that affect people of all ages and are typically associated with mild symptoms and few complications in immunocompetent individuals. However, the risk of severe outcomes (e.g., hospitalization and death) following infection with these respiratory viruses is higher in certain populations, including older adults and individuals of certain race/ethnic and sociodemographic groups. Additionally, immunocompromising conditions and pre-existing comorbidities, including underlying cardiovascular (e.g., congestive heart failure) and respiratory diseases (e.g., chronic obstructive pulmonary disease), diabetes, chronic kidney disease, and obesity, are key factors that predispose individuals to SARS-CoV-2-, influenza-, and RSV-related severe outcomes. Increased risk for severe outcomes associated with advancing age and comorbidities is compounded by residence in long-term care facilities due to the enhanced spread of respiratory infections in congregate living environments. In this narrative review, risk factors associated with severe outcomes following infection with SARS-CoV-2, influenza, and RSV in adult populations are explored. Additionally, distinct clinical outcomes based on underlying comorbidities following infection are discussed in the context of high-risk populations. Factors unique to each virus that underpin distinct risk profiles are described and suggest the potential for tailored surveillance and healthcare approaches to target and ultimately mitigate SARS-CoV-2-, influenza-, and RSV-associated disease burden in vulnerable populations. Mutual risk factors for severe outcomes are also highlighted; these similarities indicate that cohesive risk reduction strategies may also be feasible, particularly since vaccines are available for each of these respiratory viruses. Ultimately, a more thorough understanding of the risk factors that predispose individuals to develop SARS-CoV-2-, influenza-, and RSV-related severe outcomes may improve risk reduction strategies, inform healthcare policy, and contribute to the expansion and refinement of existing surveillance approaches to ultimately mitigate disease burden in vulnerable populations. Graphical Abstract Enhanced feature (slides, video, animation) (MP4 80296 KB)